2020
DOI: 10.1109/access.2020.3033058
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of SVC and STATCOM Reactive Power Compensation for Prosumer Microgrids With DFIG-Based Wind Farm Integration

Abstract: Uncertainties of renewable energy sources like wind power are one of the considerable challenges of prosumer microgrids. To meet the grid codes requirements regarding the voltage stability of wind farm integration, finding the balance between providing the demanding dynamic performance of the voltage and reactive power, and at the same time decreasing the investment on centralized reactive power compensation device, becomes an important research topic. This paper compares the effects of the static synchronous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…Reference [7] proposed a HVRT strategy based on the virtual resistance strategy by analyzing the transient process of the DFIG when facing the voltage swell problem. Other papers installed a reactive power compensation device at the grid-connection point to improve the wind farm's ride-through capability [10][11][12][13][14]. References [11][12][13] compared the reactive power compensation capabilities of static synchronous compensators (STATCOM) and static var compensators (SVC) during low voltage ride-through (LVRT) periods of wind farms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reference [7] proposed a HVRT strategy based on the virtual resistance strategy by analyzing the transient process of the DFIG when facing the voltage swell problem. Other papers installed a reactive power compensation device at the grid-connection point to improve the wind farm's ride-through capability [10][11][12][13][14]. References [11][12][13] compared the reactive power compensation capabilities of static synchronous compensators (STATCOM) and static var compensators (SVC) during low voltage ride-through (LVRT) periods of wind farms.…”
Section: Introductionmentioning
confidence: 99%
“…Other papers installed a reactive power compensation device at the grid-connection point to improve the wind farm's ride-through capability [10][11][12][13][14]. References [11][12][13] compared the reactive power compensation capabilities of static synchronous compensators (STATCOM) and static var compensators (SVC) during low voltage ride-through (LVRT) periods of wind farms. References [11,13] revealed that STATCOMs can provide more reactive power during voltage sag periods, and have a better transient performance than SVC after a voltage sag fault.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible AC transmission system (FACTS) devices have thus been developed for voltage regulation in power system applications, whereas static VAR compensators (SVCs) and static synchronous compensators (STATCOMs) play major roles by using power conversion in interior inverter designs to achieve voltage control. (2,3) Although most FACTS devices provide better performance than traditional unidirectional power flow control methods, their controllers are more expensive. (4) The benefit of reactive power compensation mainly depends on the placement and capacities of the installed FACTS devices.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the conventional PI controller and other suggested optimized algorithms in STATCOM were compared to demonstrate the efficiency of the proposed methodology25. A detailed comparison of SVC and STATCOM for transient voltage stability in DFIG based wind farm is presented in [26]. This research work proposed that STATCOM even with low capacity as compared to the SVC is more reliable and cost-effective.…”
Section: Introductionmentioning
confidence: 99%